Substance use, risk, and protective factors among Indigenous youth: an examination of evidence from recent decades - Fetterling, Theodore J., author; Prince, Mark, advisor; Riggs, Nathaniel, committee member; Emery, Noah, committee member; Swaim, Randall, committee member (Colorado State University. Libraries, 2023)
American Indian (AI) youth have consistently been identified as an at-risk population for elevated rates of substance use relative to non-AI peers. Reliance upon single-site and regional substance use research with Indigenous samples has led to substantial variability in the magnitude of estimates in the extant literature. This variability is exacerbated by demographic differences shown to influence substance use prevalence as well as the ceremonial use of tobacco in many tribes. Ceremonial practices involving tobacco also present a unique impact on perceptions of availability and harm of substances, however little research has investigated the salience of these perceptions as either risk or protective factors among AI youth. The present study addresses the variability in estimates and limited representation of AI youth by consolidating nearly three decades of repeated cross-sectional data to provide accurate and precise estimates of alcohol, cannabis, and cigarette use. The hypotheses that perceived availability and harm would differentially predict substance use among AI youth compared to White peers were also tested. Method. The sample was drawn from data collected between 1993-2019 as part of ongoing epidemiology research with reservation-dwelling AI youth and White peers. Descriptive statistics were used to provide substance use estimates for alcohol, cannabis, and cigarettes, stratified by race/ethnicity (i.e., AI vs White), grade group, sex, and region. After stratifying for demographic comparisons, estimates were presented for each year of available data and aggregated across years for all substance use variables. Binary logistic and quasi-Poisson regressions were used to test study hypotheses regarding the influence of perceived availability and harm on substance use separately for AI and White youth. A subset of years was selected for an exploratory application of time-varying effect modeling (TVEM) for trend analysis. Results. Similar patterns emerged across demographic comparisons for average cannabis use, showing elevated rates among AI youth relative to White peers. Average lifetime prevalence of cigarettes was consistently higher among AI youth than White peers, however this pattern was not found for average frequency of cigarette use or for any average alcohol use comparison. Hypotheses were partially supported, in that perceived harm was significantly more protective for White youth than for AIs, but perceived availability showed no significant differences in protective influence for lifetime prevalence comparisons of any substance. TVEM trends mirrored descriptive statistic comparisons found for stratification by race/ethnicity and region. Discussion. Findings revealed stark contrasts in rates of substance use and the influences of perceived availability and harm between AI and White youth. These differences are interpreted within the context of historical trauma (HT) and ceremonial practices involving tobacco found in many Indigenous communities. For prevention and intervention programs to be culturally responsive, they should be developed at the community level and incorporate strategies for coping with HT. Additionally, distinguishing recreational tobacco use from ceremonial use can enhance accuracy of estimates in future epidemiology research and contribute to culturally informed prevention and intervention programming for AI youth.